The role of chance in cancer causation - Angelini, Marco; Collatuzzo, Giulia; Teglia, Federica; Sassano, Michele; Siea, Andrei Cosmin; Boffetta, Paolo (La Medicina del Lavoro, 2022)
In the last years, the discussion about the role of chance in the causation of cancer has generated much scientific and public debate. The concept that chance, or “bad luck”, as responsible for a majority of the variation of cancer incidence, may be misleading, possibly causing an underestimation of the role played by known risk factors. In this commentary we discuss how host and external factors interact with chance in cancer causation in different ways, and provide examples of situations where chance appears to play only a minor role on cancer onset.